Electroreflectance of Cu₂(Cd₁-ₓ,Znₓ)SnS₄ thin film solar cells - Levcenko, S. (2022)
The effect of Cu off-stoichiometry and Zn alloying on the fundamental absorption region of (CCTS) absorbers in complete solar cells has been investigated using electroreflectance (ER) spectroscopy at room temperature. It is found that ER spectra consist of contributions from two different sources, one of which corresponds to band gap transition in the absorber layer and the other to the interference effect in the window layer. ER measurements on CCTS samples reveal a near-constant band gap energy of 1.37-1.38 eV and a relatively small broadening of 60-90 meV in the probed compositional range, in contrast to related kesterites . The analysis of the band gap in alloys yields a quadratic dependence on Zn content with a bowing parameter of 0.4 eV. Finally, the broadening parameters of the band gap transitions as well as their compositional dependence are evaluated and discussed.